Is the fish oil obtained by supercritical fluid extraction(SCFE) healthy? - Mirghani, Mohamed Elwathig Saeed; Hussein, Ismail H.; Yassin, Atif A. A. (2013)
Fish oils are a rich natural source of long-chain polyunsaturated fatty acids (PUFAs), especially those of the omega-3 series, mainly eicosapentaenoic acid (EPA) and docosahezanenoic acid (DHA). Looking for natural sources of omega-3 fatty acids, designing new methods and developing better extraction methods for obtaining omega-3 fatty acid and trying to include omega-3 fatty acids in food product of regular consumption are really demanding and challenging tasks. Response Surface Methodology (RSM) of the Design Expert (Version 6.0.8) was employed to study the main interaction effects of extraction condition from SC-CO2 on the fish oil yield. The result showed that the highest extraction oil yield was 4.51% and 5.07% for two types of fish, which obtained with temperature, pressure and extraction time at 55 ºC, 300 bars, and 80 min, respectively. The fatty acid composition of the extracted fish oil was determined using GC/MS showed that saturated fatty acids, monounsaturated fatty acids and polyunsaturated fatty acids were presented in the extracted oil. Two of monounsaturated fatty acids found in the two types of extracted fish oil, which were palmitoleic acid and oleic acid. Omega-6 fatty acid family (arachidonic) and omega-3 (EPA and DHA) were also found in both of them. The chemical properties of the fish oil including acid value (AV), saponification value (SV), iodine value (IV) and peroxide value (PV) were also investigated. The results were found to be 9.47±2.2 mg KOH/g oil, 235 ± 5.7 mg KOH/g, 138±2.35 g I/100g oil and 13.8 meq/kg, for AV, SV, IV, and PV, respectively. It was observed that though most of the results obtained were tolerable to the standard values, however some were outside the normal range especially PV that indicated such oxidation was going on. The result of AV (9.47) also indicated such hydrolysis of oil was on. Although the extracted fish oil using SCFE is pure but the question rose is it healthy?